ความสัมพันธ์ระหว่างปัจจัยด้านงบการเงินและการปรับประมาณการกำไรของนักวิเคราะห์หลักทรัพย์สำหรับบริษัทจดทะเบียน - สมรสม พานิชโยทัย (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this study is to examine the relationship between financial statement factors and analysts earnings forecast revisions. This empirical research samples are companies listed in the Stock Exchange of Thailand during the year 2002 to 2006. This study apply correlation analysis and cross-sectional multiple regression analysis to test the relationship between financial statement factors and analysts earnings forecast revisions. The variables examined in this study are financial statement factors including inventory signal, accounts receivable signal, gross margin signal, capital expenditures signal, selling and administrative expenses signal, leverage signal and audit opinion modified for scope limitation, going concern and other uncertainty. The study finds that gross margin signal, selling and administrative expenses signal, leverage signal and audit opinion modified for scope limitation have significantly negative relationship with analysts earnings forecast revisions, whereas accounts receivable signal has significantly positive relationship with analysts earnings forecast revisions. The results suggest that analysts are aware of the future earnings information embedded in some of the financial statement factors and respond to them by revising their earnings forecast upward (downward) if it is positive (negative) signal. However, the factors including inventory signal, capital expenditures signal and audit opinion modified for going concern and other uncertainty are not found to be significantly related with analysts earnings forecast revisions. This result also indicates that analysts revisions of earnings forecast are not affected by these factors